Interpretation of Mismatch Repair Protein Immunohistochemistry in Endometrial Carcinoma Should Consider Both Lynch Syndrome Screening and Immunotherapy Susceptibility: An Illustrative Case Report. (May 2020) - Chapel, David B.; Lengyel, Ernst; Ritterhouse, Lauren L.; Lastra, Ricardo R.
Abstract : Supplemental Digital Content is available in the text. Abstract : We present an instructive case of FIGO grade 1 endometrioid endometrial carcinoma with a biphasic morphology, corresponding to subclonal loss of mismatch repair proteins (MMRP) MLH1 and PMS2 by immunohistochemistry and subclonal microsatellite instability. A pulmonary metastasis represented only the tumor component with retention of MMRPs. This case illustrates the need for pathologists to recognize and report heterogenous expression of MMRPs in endometrial carcinoma, to consider tumor heterogeneity when selecting foci for molecular studies, and to re-evaluate MMRP expression in tumor metastases, when clinically indicated. These considerations are particularly important as the relevance of MMRP expression in endometrial cancer expands beyond Lynch syndrome screening, into a new role as a predictive marker for immunotherapy.